Fontes de energia, posição trófica e digestibilidade de peixes de diferentes níveis tróficos da planície de inundação do alto rio Paraná. - Faria, Anna Christina Esper Amaro de (2007)
This thesis take part of the LTER program (Long Term Ecological Research) developed by Research Nucleus in Limnology, Ichthyology, and Aquaculture (Nupelia), entitled "Floodplain system of the Paraná river: environmental structures and processes" which aims to establish the structure and functioning of food web in this ecosystem. There were made two chapters: Chapter 1 aiming to investigate the isotopic variability of δ15N, characterize the trophic position and identify energy autotrophic sources to different commercial fish species in the ecological system of the floodplain of the Parana River that's consists of rivers, canals and lagoons. This system is very complex, as regards the flow of energy in its biological compartments and species of fish belonging to different trophic groups. Thus, the use of stable isotope analysis in ecological studies in these environments have helped to delineate and understand the dynamics of carbon sources and their flow in the organisms producers, consumers and decomposers in food webs. Chapter 2 aiming to evaluate the quality and digestibility of food consumed by fish belonging to different trophic groups of the floodplain of the Upper Paraná River. Investigations associated with isotopic studies of the nutritional quality of major food resources and the digestibility of the food consumed by fish, determine the quantities available and assimilation of different local by fish of different trophic categories, allowing for better understanding of how species occupy different environmental compartments. This information, once available, will assist in the preparation of the most representative models of energy flow, since it allows to assess the actual assimilation of energy transferred from one trophic level to another, vital to understanding the structure and functioning of this ecosystem.